2010
DOI: 10.3758/pbr.17.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Contingency is used to prepare for outcomes: Implications for a functional analysis of learning

Abstract: It is generally assumed that the function of contingency learning is to predict the occurrence of important events in order to prepare for them. This assumption, however, has scarcely been tested. Moreover, the little evidence that is available suggests just the opposite result. People do not use contingency to prepare for outcomes, nor to predict their occurrence, although they do use it to infer the causal and predictive value of cues. By using both judgmental and behavioral data, we designed the present exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…In addition to active vs. passive roles of participants, there are many other variants that can be introduced in this task and that have been shown to affect the participants’ estimations of causality. Examples include changing the wording of questions asked at the end of the experiment about the causal relationship ( Crocker, 1982 ; Vadillo et al, 2005 , 2011 ; Collins and Shanks, 2006 ; De Houwer et al, 2007 ; Blanco et al, 2010 ; Shou and Smithson, 2015 ), the order in which the different trial types are presented ( Langer and Roth, 1975 ; López et al, 1998 ), the frequency with which judgments are requested ( Collins and Shanks, 2002 ; Matute et al, 2002 ), the description of the relevant events as causes, predictors, or effects ( Waldmann and Holyoak, 1992 ; Cobos et al, 2002 ; Pineño et al, 2005 ), the temporal contiguity between the two events (e.g., Shanks et al, 1989 ; Wasserman, 1990 ; Lagnado and Sloman, 2006 ; Lagnado et al, 2007 ), and many other variables that fortunately are becoming well known. In the following sections, we will focus on the variables that seem to affect the illusion most critically in cases of null contingency.…”
Section: How To Assess the Illusionmentioning
confidence: 99%
“…In addition to active vs. passive roles of participants, there are many other variants that can be introduced in this task and that have been shown to affect the participants’ estimations of causality. Examples include changing the wording of questions asked at the end of the experiment about the causal relationship ( Crocker, 1982 ; Vadillo et al, 2005 , 2011 ; Collins and Shanks, 2006 ; De Houwer et al, 2007 ; Blanco et al, 2010 ; Shou and Smithson, 2015 ), the order in which the different trial types are presented ( Langer and Roth, 1975 ; López et al, 1998 ), the frequency with which judgments are requested ( Collins and Shanks, 2002 ; Matute et al, 2002 ), the description of the relevant events as causes, predictors, or effects ( Waldmann and Holyoak, 1992 ; Cobos et al, 2002 ; Pineño et al, 2005 ), the temporal contiguity between the two events (e.g., Shanks et al, 1989 ; Wasserman, 1990 ; Lagnado and Sloman, 2006 ; Lagnado et al, 2007 ), and many other variables that fortunately are becoming well known. In the following sections, we will focus on the variables that seem to affect the illusion most critically in cases of null contingency.…”
Section: How To Assess the Illusionmentioning
confidence: 99%
“…For instance, participants learn to navigate through a three-dimensional space while interacting with "characters" later used for identification tests (Wade & Holt, 2005). Arcediano, Ortega, and Matute (1996) developed the "Martians" game to explore classical conditioning using Martians and explosions as stimuli (see also Baeyens et al, 2005;Blanco, Matute, & Vadillo, 2010;Franssen, Clarysse, Beckers, van Vooren, & Baeyens, 2010). Gamelike tasks have been used to study instrumental learning with stimuli presented as balloons that must be shot from the sky (Krageloh, Zapanta, Shepherd, & Landon, 2010), minefields to be navigated (Baker, Mercier, Vallee-Tourangeau, Frank, & Pan, 1993), or a host of similar examples (Lie, Harper, & Hunt, 2009;Molet, Jozefowiez, & Miller, 2010;Paredes-Olay, Abad, Gamez, & Rosas, 2002;Stokes & Balsam, 2001;Stokes & Harrison, 2002).…”
Section: Gaming-up Experimentsmentioning
confidence: 99%
“…Behavioral experiments with human ( Blanco et al, 2010 ) and non-human animals (e.g., Hallam et al, 1992 ; Murphy & Baker, 2004 ; Rescorla, 1968 ) had already shown that preparatory behavior is influenced by the reliability of the signals or, in other words, by signal–outcome contingency. Those experiments had typically maintained P ( O | S ) constant, so that contingency between the signal and the outcome could be manipulated and its effect on behavior established.…”
Section: Discussionmentioning
confidence: 99%
“…Following Blanco et al’s (2010) experiment we used the Martians task ( Arcediano et al, 1996 ; Costa & Boakes, 2011 ; Franssen et al, 2010 ; Matute et al, 2007 ). This allows us to assess how P ( O | S ) affects the participants’ anticipatory behavior directly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation